Thrombophilia Caused by Beta2-Glycoprotein I Deficiency: In Vitro Study of a Rare Mutation in APOH Gene - Zhang, Xiao-ping; Zeng, Wei; Liu, Hui; Tang, Liang; Wang, Qing-yun; Cheng, Zhi-peng; Wu, Ying-ying; Hu, Bei; Shi, Wei; Hu, Yu (Current medical science, 2018)
Summary This study aimed to explore the mechanism of a novel mutation ( p.Lys38Glu ) in apolipoprotein H (APOH) gene causing hereditary beta2-glycoprotein I (β2GPI) deficiency and thrombosis in a proband with thrombophilia. The plasma level of β2GPI was measured by ELISA and Western blotting, and anti-β2GPI antibody by ELISA. Lupus anticoagulant (LA) was assayed using the dilute Russell viper venom time. Deficiency of the major natural anticoagulants including protein C (PC), protein S (PS), antithrombin (AT) and thrombomodulin (TM) was excluded from the proband. A mutation analysis was performed by amplification and sequencing of the APOH gene. Wild type and mutant ( c.112A > G ) APOH expression plasmids were constructed and transfected into HEK293T cells. The results showed that the thrombin generation capacity of the proband was higher than that of the other family members. Missense mutation p.Lys38Glu in APOH gene and LA coexisted in the proband. The mutation led to β2GPI deficiency and thrombosis by impairing the protein production and inhibiting the platelet aggregation. It was concluded that the recurrent thrombosis of the proband is associated with the coexistence of p.Lys38Glu mutation in APOH gene and LA in plasma.